Human Resource Planning in Building Employee Commitment Amidst the Challenges of Mental Health Issues - Saksono, Lalang; Antonio, Ferdi; Sukirman, Sukirman; Lubis, Fatimah Malini; Santosa, Sonny (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Current issues in human resource management include various challenges and trends faced by companies today. This study aims to provide an understanding of the literature on human resource planning in building employee commitment amidst the challenges of mental health issues. This study uses literature research to realize the objectives of this study. The written sources used in this study certainly come from secondary data. The secondary data in question are written sources such as books, journals, articles, and research reports. The results of the study showed that Clark's theory explains that proper human resource planning will create good mental health, which has a positive impact on building employee commitment and efforts to balance work life with personal life, which can affect employee mental health.